Caffeine degradation by Rhizopus delemar in packed bed column bioreactor using coffee husk as substrate - Tagliari,Cristiane Vanessa (2003)
Various microorganisms including bacteria, yeast and fungi can degrade caffeine. There are few publications about caffeine degradation pathway in filamentous fungi, mainly by solid-state fermentation (SSF). Studies were carried out on degradation of caffeine and their metabolites by filamentous fungi in SSF using coffee husk as substrate. The purpose of this work was to investigate the caffeine degradation pathway by Rhizopus delemar in packed bed column fermenter and to compare this degradation metabolism with glass flasks fermentation. The methylxanthines were quantified by HPLC analysis. The experiments were realized with the optimized conditions in previous experiments: pH 6.5, 28ºC, inoculation rate 10(6) spores/g substrate, aeration rate 60 mL/min and initial moisture 73%. Under these conditions, after 72 hous of fermentation was achieved only 0.19% of caffeine and 0.014% of theophylline in the coffee husk. The strain proved to be able for caffeine and theophylline degradation by SSF in packed bed column bioreactor.